The pathogenic N650K variant in the GluN1 subunit regulates the trafficking, conductance, and pharmacological properties of NMDA receptors - Kolcheva, Marharyta; Ladislav, Marek; Netolicky, Jakub; Kortus, Stepan; Rehakova, Kristyna; Krausova, Barbora Hrcka; Hemelikova, Katarina; Misiachna, Anna; Kadkova, Anna; Klima, Martin; Chalupska, Dominika; Horak, Martin (Neuropharmacology, 2023)
N-methyl-D-aspartate receptors (NMDARs) play an essential role in excitatory neurotransmission in the mammalian brain, and their physiological importance is underscored by the large number of pathogenic mutations that have been identified in the receptor's GluN subunits and associated with a wide range of diseases and disorders. Here, we characterized the functional and pharmacological effects of the pathogenic N650K variant in the GluN1 subunit, which is associated with developmental delay and seizures. Our microscopy experiments showed that when expressed in HEK293 cells (from ATCC®), the GluN1-N650K subunit increases the surface expression of both GluN1/GluN2A and GluN1/GluN2B receptors, but not GluN1/GluN3A receptors, consistent with increased surface expression of the GluN1-N650K subunit expressed in hippocampal neurons (from embryonic day 18 of Wistar rats of both sexes). Using electrophysiology, we found that the GluN1-N650K variant increases the potency of GluN1/GluN2A receptors to both glutamate and glycine but decreases the receptor's conductance and open probability. In addition, the GluN1-N650K subunit does not form functional GluN1/GluN2B receptors but does form fully functional GluN1/GluN3A receptors. Moreover, in the presence of extracellular Mg2+, GluN1-N650K/GluN2A receptors have a similar and increased response to ketamine and memantine, respectively, while the effect of both drugs had markedly slower onset and offset compared to wild-type GluN1/GluN2A receptors. Finally, we found that expressing the GluN1-N650K subunit in hippocampal neurons reduces excitotoxicity, and memantine shows promising neuroprotective effects in neurons expressing either wild-type GluN1 or the GluN1-N650K subunit. This study provides the functional and pharmacological characterization of NMDARs containing the GluN1-N650K variant.
Keywords: Memantine; savci; Ketamine; Humans; Female; Glutamic Acid; Receptors, N-Methyl-D-Aspartate; krysa rodu Rattus; lidé; HEK293 Cells; zvířata; Mammals; potkani Wistar; receptory N-methyl-D-aspartátu; Neurodegeneration; ženské pohlaví; Rats, Wistar; Male; Glutamate receptor; HEK293 buňky; Rats; Animals; Hippocampal neuron; mužské pohlaví; Ion channel; kyselina glutamová; memantin